Speriolin is a novel human and mouse sperm centrosome protein - Goto, M. (Oxford University Press, 2010)
BACKGROUND: Oocytes in humans, mice and other mammals lack identifiable centrioles. The proximal centriole brought in by the fertilizing sperm in humans and most other mammals appears to gives rise to the centrioles at the spindle poles in the zygote, and is believed to indicate that centrioles are inherited through the paternal lineage. However, both the proximal and distal sperm centrioles degenerate in mice and other rodents. A bipolar mitotic spindle nucleates from multiple centrosome-like structures in the mouse zygote and centrioles are not seen until the blastocyst stage, suggesting that centrioles are inherited through the maternal lineage in mice. We previously identified speriolin as a spermatogenic cell-specific binding partner of Cdc20 that co-localizes with pericentrin in mouse spermatocytes and is present in the centrosome in round spermatids. METHODS: The nature and localization of speriolin in mouse and human sperm and the fate of speriolin following fertilization in the mouse were determined using immunofluorescence microscopy, immunoelectron microscopy and western blotting. RESULTS: Speriolin surrounds the intact proximal centriole in human sperm, but is localized at the periphery of the disordered distal centriole in mouse sperm. Human speriolin contains an internal 163-amino acid region not present in mouse that may contribute to localization differences. Speriolin is carried into the mouse oocyte during fertilization and remains associated with the decondensing sperm head in zygotes. The speriolin spot appears to undergo duplication or splitting during the first interphase and is detectable in 2-cell embryos. CONCLUSIONS: Speriolin is a novel centrosomal protein present in the connecting piece region of mouse and human sperm that is transmitted to the mouse zygote and can be detected throughout the first mitotic division.